2007
DOI: 10.1017/s0950268807008266
|View full text |Cite
|
Sign up to set email alerts
|

Standardization of measles, mumps and rubella assays to enable comparisons of seroprevalence data across 21 European countries and Australia

Abstract: SUMMARYThe aim of the European Sero-Epidemiology Network is to establish comparability of the serological surveillance of vaccine-preventable diseases in Europe. The designated reference laboratory (RL) for measles, mumps, rubella (MMR) prepared and tested a panel of 151 sera by the reference enzyme immunoassay (rEIA). Laboratories in 21 countries tested the panel for antibodies against MMR using their usual assay (a total of 16 different EIAs) and the results were plotted against the reference results in orde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
50
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 30 publications
(50 reference statements)
3
50
1
Order By: Relevance
“…This result contrasts with results for measles serology, which has better correlation between PRN and whole-virus ELISA and for which PRN is considered the most sensitive testing method ( [42][43][44][45][46]. In addition, measles serology benefits from having an international reference standard with a level of neutralizing activity that correlates with protection (47).…”
Section: Discussionmentioning
confidence: 77%
“…This result contrasts with results for measles serology, which has better correlation between PRN and whole-virus ELISA and for which PRN is considered the most sensitive testing method ( [42][43][44][45][46]. In addition, measles serology benefits from having an international reference standard with a level of neutralizing activity that correlates with protection (47).…”
Section: Discussionmentioning
confidence: 77%
“…In cases where one result was o10 IU/ml and one <10 IU/ml, the lowest result was reported in clinical practice. Attempts to standardize rubella status reporting have recently been made, one 2007 study examined results of antibody testing performed by reference laboratories in 21 countries [17]. Researchers defined a cut-off of <4 IU/ml as seronegative, 4-7 IU/ml as equivocal and >7 IU/ml as seropositive.…”
Section: Methodsmentioning
confidence: 99%
“…It was stated, however, that for women of childbearing age the defined cut-off for immunity should be an antibody titre >10 IU/ml [17,18]. The Diasorin assay used in this laboratory was used by four of the 21 reference laboratories and gave 100 % agreement on testing the negative samples but an underestimation of antibody in the positive samples [17]. A 2008 study of eight EIA kits including the Diasorin, Abbott and bioMe´rieux kits demonstrated that these kits had comparable sensitivity and specificity with no false-positive results [16].…”
Section: Methodsmentioning
confidence: 99%
“…This methodology has been applied successfully for various vaccine-preventable infections during the ESEN projects, i.e. : (i) measles, mumps, rubella [16,20] ; (ii) pertussis [17] ; (iii) diphtheria [19]) ; (iv) VZV [18] ; and (v) HBV [21]. The present collaborative work describes the development of a standardization procedure that allows for direct comparisons of HAV seroprevalence data generated at 15 European laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…However, inter-laboratory variation, even when using the same EIA and international standards, is a well-recognized problem [15][16][17][18][19][20][21]; accordingly, differences mostly in sensitivity, but also in specificity, have been reported for both commercial and in-house anti-HAV assays [22][23][24][25][26][27][28][29][30][31]. Standardization is a methodological approach that provides a means to overcome this limitation and to ensure the direct comparability of seroepidemiological results obtained during the project [32].…”
Section: Introductionmentioning
confidence: 99%